A new strategy and fewer forces : the Pacific dimension - Winnefeld, James A., 1929-; Pollack, Jonathan D.; Lewis, Kevin N. (Kevin Neil), 1955-; Pullen, L. D.; Schrader, John Y.; Swaine, Michael D., 1951-; Rand eBooks (Santa Monica, CA : RAND, 1992)
This report considers how the United States should reposture its forces, adjust its policies, and change its military operations in the Asia-Pacific region, all in the context of reduced resources and increased burden-sharing by allies and security partners. It assesses six alternative U.S. regional force postures that might develop over the next 15 years. Each posture is examined from three perspectives: (1) regional responses to the posture, (2) performance in hypothetical contingencies if deterrence fails; and (3) comparative cost. The analysis indicates that the base force posture reflected in the current Future Year Defense Plan is probably the best compromise now for sufficient reassurance of U.S. security partners, deterrence of possible opponents, adequate performance in representative contingencies, and acceptable cost. If threats and uncertainties decline markedly, somewhat lower postures would be acceptable. Risks start to increase rapidly at postures below the base force level. The authors recommend a variety of threat reduction, posture enhancement, and hedging measures.
Research "developed by the staff of the RAND Strategy Assessment Center ... part of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references (p. 135-143).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Asia -- Defenses; Pacific Area -- Defenses; United States -- Armed Forces -- Defenses; United States -- Armed Forces -- Pacific Area; Electronic books